Implementation Of Guidance And Counseling Program In Madrasah Aliyah Islamic Boarding School Darul Ulum Asahan - Abdurrahman, Tien Rafida, Riswan Hadi (International Journal Of Education, Social Studies, And Management (IJESSM), 2021)
This study aims to explore in-depth data about the implementation of the field of academic guidance services, personal guidance services, social guidance services, and student career guidance services at Madrasah Aliyah Private Islamic Boarding School Modern Darul Ulum Asahan with qualitative research methods with data collection techniques through observation instruments, interviews. and documentation studies. The informants in this study were counseling teachers, madrasa principals, and students. The results of this study explain that: 1) The implementation of services in the field of academic guidance at the Darul Ulum Asahan Modern Private Islamic Boarding School has been carried out properly by providing COUNSELING GUIDANCE program services that lead to the student's academic field. help students solve learning problems that occur to them. The role of COUNSELING GUIDANCE teachers, school principals, and the curriculum has been carried out, but only limited time in providing guidance and counseling programs. The implementation of personal guidance in Private Madrasah Aliyah, 2) Modern Darul Ulum Asahan Islamic Boarding School, is carried out well by giving students directions to students to be able to solve personal problems that exist in themselves and develop their abilities or potentials. The role of guidance and counseling teachers is also as expected in providing services related to personal guidance. which is wherein the implementation of services in the field of personal guidance the guidance and counseling teacher efforts to develop the talents, potentials, and skills of each student by inviting students to be more creative and productive in supporting their potential, such as providing facilities and infrastructure that can generate ideas Student creativity, 3) Implementation of social guidance services in the Private Madrasah Aliyah Islamic Boarding School Modern Darul Ulum Asahan has been socially progressing properly by providing guidance and counseling program services that lead to the field of social development. The role of guidance and counseling teachers in the form of orientation, information, placement, and group guidance services where students are led to be more active in communicating, interacting, and socializing with their environment, and 4) service delivery in the field of career guidance at the Private Madrasah Aliyah Islamic Boarding School Modern Darul Ulum Asahan is carried out by providing understanding to students related to understanding, planning, choosing, adjusting and developing a career according to their interests and talents.